The Natural Resource Curse: Is It Really a Curse? - Algharabali, Barrak Ghanim; Al-Thaqeb, Saud Asaad (International Journal of Energy Economics and Policy, 2023)
The Natural Resource Curse literature started with a clear consensus that dependence on natural resources have clear direct negative effects on economic growth and levels of democracy. However, the literature today reflects that the debate is still going where several papers reflects evidence that is against the consensus of the Natural Resource Curse hypothesis, which provides many open avenues for further research. This paper surveys the literature of the natural resource curse and identifies the main arguments and findings of both streams (curse stream and blessing stream). The main point that this paper highlights is that the literature is still not clear 100% whether the natural resource is a curse or a blessing. The econometric technique and the way how you define natural resources could lead to different or opposite results.